The seed husk bran of Moringa oleifera improves the nutritional and sensory quality of bakery cookies - Almora-Hernández, Ernesto (2023)
Today, 70% of the food supply comes from just three grains (corn, wheat and rice) but we rely on few grains. The search for the use of agro-industrial residues in industrial processing has led to obtaining unconventional products that constitute raw materials for human food. The objective of the work was to enrich baked cookies with the addition bran from seed husk of Moringa oleifera. The bran was obtained from the shell of Moringa seeds during the shelling process, which was washed, dried and ground. The bran was added in doses of 5, 10 and 15% to the formulation of the baked cookies. Microbiological analysis was carried out, physicochemical characterization by near-infrared spectroscopy, and sensory evaluation were performed on 109 untrained consumers, using a seven-point hedonic test. The microbiological analysis was satisfactory, while the proximal analysis of the bran showed a percentage of fiber, protein, fat, carbohydrates, ashes and moisture of 37.21, 22.97, 13.09, 12.64, 7.04 and 5.82%; respectively. After baking the cookies, the proximal characterization expressed a percentage of protein between 9.01 and 9.59%, fat from 11 to 13.27%, ashes from 0.96 to 0.98%, fiber from 4.33 to 6.21% and starch between 57.62 and 59.04%. The highest percentage of liking with 67.89% was presented in the "I like" category in the cookies with 5% bran and with a level of preference also those of 5% (51.38%). It was concluded that the bran from the husk of Moringa seeds produces an increase in nutritional value and sensory quality of the baked cookies.